SHG-Bank Linkage Programme in India: An Appraisal of Trends and Issues - Bera, Sayantan (Indian Journal of Finance, 2009)
Figures from the NABARD flagship SHG-bank linkage programme indicates a sustained progress in terms of number of SHGs credit linked and bank loan disbursed. But agency-wise performance in promoting SHGs indicates an unequal performance among and within agencies, driven mostly by star performers. A close look at the figures also reveals that more than three-fourth of the already existing SHGs did not receive any repeat loans during 2005-06: a disturbing trend that has been continuing for years. The trend in declining rural bank branches, lack of voluntary savings facilities and several others highlighted in this paper also demand attention from all stakeholders. Finally, with reasonable apprehension, we note that trading ‘quality’ for numbers may seriously undermine the actual purpose behind the SHG movement, namely that of financial inclusion and empowerment.